A theory for resolving qualification conflicts in double taxation treaties - Mabasa, Sbusiso Huzlett (My University, 2016)
Tax treaties have a developed language of their own within the field of international law. They may include terms that are unknown in particular jurisdictions of domestic law or therein defined differently. Because the language of tax treaties and domestic law differ from each other, the definitions of certain terms and income type under a tax treaty and under different states’ domestic law are not necessary identical. Despite these differences, tax treaty definitions must be used for tax treaty classification purposes, and domestic law definitions must be used for domestic law classification purposes. The tax definition determines the type of the income for tax treaty purposes even though the income would qualify under another income category under the treaty states’ domestic law. Similarly, the domestic tax law definition determines the type of income for domestic law purposes (Helminen 2010). In most instances the treaty definitions of the various types of income refer back to domestic tax law, and where the domestic tax law definition deviates between the two treaty countries, this may lead to the application by these countries of different articles of the treaty. If this is caused by the application of the domestic law, this is referred to as a conflict of qualification in the Commentaries to the OECD Model Tax Convention. In general a conflict of qualification refers to a situation where identical facts are treated differently for tax purposes in different countries. Such a conflict may either concern the subject or the object of taxation. Key words: Tax treaties, OECD MTC, Double Tax Agreements, double taxation, conflicts of qualification, hybrid entities, partnerships, fiscally transparent, domestic law, Mutual Agreement Procedures, permanent establishment.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Commerce (Taxation). Johannesburg, 2015
Keywords: Tax treaties; OECD MTC; Double tax agreements; Conflicts of qualification; Hybrid entities; Partnerships